Food matrix impacts bioaccessibility and assimilation of acid whey-derived milk fat globule membrane lipids in Caco-2 cells - Kosmerl, Erica; Martínez-Sánchez, Victoria; Calvo, María V.; Jiménez-Flores, Rafael; Fontecha, Javier; Pérez-Gálvez, Antonio (Frontiers in Nutrition, 2023)
The milk fat globule membrane (MFGM) imparts human health benefits ranging from improved immune system, gut, and brain function to improved cardiometabolic health. The expanding applications of MFGM-enriched ingredients demand evidence-based formulation to adequately deliver their benefits and improve bioaccessibility. In this study, the impact of food matrices and supplementation levels on the bioaccessibility and assimilation of MFGM lipids in cell culture was investigated. An MFGM ingredient derived from cottage cheese acid whey was supplemented at 2, 5, or 10% (w/w) into 3 food matrices: protein-rich (jelly), carbohydrate-rich (cookie), and carbohydrate- and fat-rich (cookie with sunflower oil (SF-cookie)). Each formulation underwent simulated digestion consisting of oral, gastric, and intestinal phases, and the micellar fraction was collected for both analysis and lipid assimilation in Caco-2 intestinal cells. The micellar fractions were diluted and applied to the cells for 4 h. A lipidomic approach was used to assess the lipid profiles of micellar fractions and intestinal cells. The micelles from digested jellies, cookies, and SF-cookies containing MFGM showed a distinct separation using partial least squares discriminant analysis (PLS-DA). Both correlation loadings and VIP scores demonstrated a preference of MFGM polar lipids (ceramides, glucosylceramides) for micelles from digested jelly, whereas micelles from digested cookies were associated with MFGM neutral lipids (free fatty acids, cholesterol, etc.). The effect of supplementation level on the micellar lipid profiles reinforced this pattern. The lipid profiles of intestinal cells after incubation with the micellar fractions differed considerably from the corresponding micellar lipid profiles. Specifically, the SF-cookie-treated cells were associated with a greater abundance of PUFA relative to jelly- and cookie-treated cells; however, increasing MFGM supplementation showed irregular patterns and rearrangement of cellular lipid profiles, suggesting the cells’ role in regulating lipid metabolism in response to nutritional stimuli. The nature of lipid micellarization and assimilation in intestinal cells from MFGM-containing food formulations echoes the complexity of lipids inherent to the MFGM itself, suggesting the need for application-based MFGM supplementation.